Salt-Resistive Photothermal Materials and Microstructures for Interfacial Solar Desalination - Yu, Xiaoqiang; Zhang, Qian; Liu, Xin; Xu, Ning; Zhou, Lin (Frontiers in Energy Research, 2021)
Solar interfacial evaporation, featured by high energy transfer efficiency, low cost, and environmental compatibility, has been widely regarded as a promising technology for solar desalination. However, the interplay between energy transfer and water transport in the same channels suggests that the tradeoff between high efficiency and long-term stability inherently exists in conventional photothermal nanomaterials. We summarize state-of-the-art research on various anti-salt clogging photothermal microstructures as long-term stable interfacial solar evaporators for solar desalination. The review starts with an overview of the current status and the fundamental limit of photothermal materials for solar desalination. Four representative strategies are analyzed in detail with the most recent experimental demonstrations, including fluid convection enhancement, surface wettability engineering, energy-mass-path decoupling, and surface chemistry engineering. Finally, this article focuses on the challenges in anti-salt clogging solar interfacial evaporators and potential point-of-use applications in the future.